The roles of the US National Library of Medicine and Donald A.B. Lindberg in revolutionizing biomedical and health informatics. (6th November 2021) - Miller, Randolph A; Shortliffe, Edward H
Abstract: Over a 31-year span as Director of the National Coordination Office for High Performance Computing and Communications, Donald A.B. Lindberg, MD, and his extraordinary NLM colleagues fundamentally changed the field of biomedical and health informatics—with a resulting impact on biomedicine that is much broader than its influence on any single subfield. This article provides substance to bolster that claim. The review is based in part on the informatics section of a new book, "Transforming biomedical informatics and health information access: Don Lindberg and the US National Library of Medicine" (IOS Press, forthcoming 2021). After providing insights into selected aspects of the book's informatics-related contents, the authors discuss the broader context in which Dr. Lindberg and the NLM accomplished their transformative work.